Identifikasi Usaha Konservasi Air Tanah Pada Kelurahan Bekasi Jaya Kecamatan Bekasi Timur - Shafira Adlina (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2011)
The objective of this survey is to identify types of water conservation methods applied by the local government and the society at the Bekasi Jaya District (Kelurahan Bekasi Jaya), of the East Bekasi Region. Surveys were conducted at nine groups of households  (Rukun Wilayah) that had history of flood during the rainy season and/or drought during the dry season. Questionnaires were used to collect information from 214 respondents.  Additional data were collected through  in-depth interviews with local authorities and few residents who were familiar with the water conservation activities in the region. This survey revealed that there is no proper conservation method applied in all studied areas. Lack of conservation efforts include both minimum activity of extension by the local authority on the important of water conservation, as well as applied conservation programs in the field.  Only three households have some kind of water conservation method in place i.e. by making water collecting wells and ponds. However, these wells and ponds were not structurally up to the standard and need much improvement.  As much as 46% of the respondents had flood experience. We identified several contributing factors to these water issue, among others : 1) High rate of population growth in this area; 2) Lack of water absorption areas (vegetative-covered areas); 3) River shallowness due to household wastes that were thrown into the river; and 4) The presence of building around the river banks. Active role of government to conserve water in this region and to develop this area with the principle of sustainable is absolutely required as should be done as soon as possible.